Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan di Coffee Shop Triple Market Kemang Pratama Bekasi - Nabila, Alzahra Putri; Z, Zahra; Rosihana, Athiy Dina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The main purpose of this study is to figure out how Triple Market Kemang Pratama Bekasi Customer Loyalty, Service Quality, and Customer Satisfaction are connected. The coffee business is becoming more and more competitive, therefore it's important to provide great service, particularly from baristas, to attract and keep consumers. The study asked 70 people who go to the place often to fill out a survey. We used multiple linear regression to look at the data after doing a number of preliminary checks, such as tests of validity, reliability, and classical assumptions. A questionnaire was used to get the data. The study found that there is a statistically significant link between customer loyalty and both service quality (X1) and customer satisfaction (X2). The significance levels for both variables are 0.000 and 0.016, respectively. When these two things are put together, they have a big effect on how loyal customers are. These two variables explain 73.2% of the difference in customer loyalty, whereas other factors explain the other 26.8%.